Influences of age and gender on operative risks following carotid endarterectomy: A systematic review and meta-analysis - Nantakool, S; Chuatrakoon, B; Orrapin, S; Leung, YYR; Howard, DPJ; Rerkasem, A; Derraik, JGB; Rerkasem, K (Public Library of Science, 2023)
Objectives: This review aims to undertake a comprehensive review of the literature and investigate associations of age and gender on 30 days post carotid endarterectomy (CEA) and up to 5 years post CEA stroke, death, and combined stroke and death. Design: A systematic review and meta-analysis. Methods: Three main electronic databases including the Cochrane Library, MEDLINE, and Embase were searched from their inception to July 2022. Studies examining operative risks (i.e., stroke, death, and combined stroke and death following CEA) linked to age or gender were included. Two independent reviewers were responsible for study selection, quality assessment, and data extraction. Odds ratio (OR) and 95% confidence interval (CI) of all outcomes were calculated. Results: 44609 studies were retrieved from the search. There were 127 eligible studies (80 studies of age, 72 studies of gender, 25 studies of age and gender) for pooling in the meta-analysis. With regards to stroke and death risks within 30 days post CEA; patients aged ≥75 had higher death (OR 1.38; 95% CI 1.10–1.75) than patients aged <75. Patients aged ≥80 had higher stroke risk (OR 1.17; 95% CI 1.07–1.27) and death risk (OR 1.85; 95% CI 1.48–2.30) particular in asymptomatic patients (OR 2.4; 95% CI 1.56–3.81). Pooled effect estimates by gender, at 30 days post CEA, showed that female was associated with increased risk of stroke (OR 1.28; 95% CI 1.16–1.40), with more risk in asymptomatic female patients (OR 1.51; 95% CI 1.14–1.99). Conclusions: This meta-analysis highlights that older people is associated with increased stroke risk, particularly asymptomatic octogenarians who had higher likelihood of death within 30 days post CEA. In addition, female especially those with asymptomatic carotid stenosis had greater likelihood of stroke within 30 days post CEA surgery.